Pendugaan umur simpan metode extend storage studies dan pengaruh lama penyimpanan terhadap organoleptik simplisia Mentha x piperita L - Safrina, Devi; Lestari, Putri (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2021)
Mentha x piperita L. simplicialÂ may undergo deterioration during storage, therefore it is very important to determine its shelf life. The determination of shelf life was done using Extend Storage Studies (ESS) method. This study was aimed to determine the shelf life and the effect of storage time on organoleptic simplicia M. x piperita. The sample used was simplicia that has been stored for 0, 15, 22, 30, 32, and 44 mounth in the simplicia storage warehouse with some long storage, and then the samples were subjected for moisture content analysis and organoleptic evaluation. The results showed that the shelf life of M. x piperita simplisia determined using the method of a water content parameter approach was 27 months. After 27 months of storage, although the aroma still can be preserve, there wa a decrease in the tasteÂ and the color of simplisia.Â In addition, there was increase in water content.